Screening of Rhizosphere Bacteria from Clove (Syzygium aromaticum) in Tidore Island as Plant Growth Promoting Rhizobacteria - Ismat Ishak; Tri Ardyati; Luqman Qurata Aini (Journal of Experimental Life Science)
Tidore Island in North Maluku Province is one of the clove (Syzygium aromaticum) producing regions. Clove plant fertility is maintained even though it is not given organic and inorganic fertilizers, it also keeps the fertility of the soil and the environment as a whole. Therefore, this study aims to explore bacteria in the rhizosphere of the clove trees planted in Tidore island as biofertilizer agents of Indol-3-Acetic Acid (IAA) production, phosphate solubilization, and ammonium production. Bacteria were isolated from the rhizosphere of clove trees. Screening of the isolates was done according to qualitative and quantitative methods. Data collection of the qualitative method were based on medium color changes for each variable while that the quantitative method (i.e. the concentrations of produced IAA, solubilized phosphate, and produced ammonium) were obtained based on spectrophotometry. The results obtained 110 bacterial isolates. Nineteen bacteria were potential as biofertilizer agents, of which isolate R11, R8P, and A1N showed the highest in IAA production (8.71 μgL-1), phosphate solubilization (8.37 μgL-1), and ammonium production (11.71 μgL-1), respectively. The three isolates respectively have similarities to the genus of Enterobacter, Burkholderia, and Stenotrophomonas.